Study on a Stratified Sampling Investigation Method for Resident Travel and the Sampling Rate - Fei Shi (Discrete Dynamics in Nature and Society)
This text first dissected the relationship between average travel frequency, trip mode structure, and the characteristics of residential areas. The results showed that conducting a stratified resident travel investigation in accordance with the characteristics of residential areas will yield samples with much smaller differences and reduce the investigation sampling rate. Accordingly, a new type of resident travel investigation method was put forward based on the above ideas. The stratified sampling rate formula and the sampling rate of each layer have been derived in detail according to Probability Theory and Mathematical Statistical Methods. Finally, for the main urban area of Kunshan City in Jiangsu province, China, we discussed the reasonable values of parameters in the formulas and obtained sampling rates for travel surveys in different residential areas. Theory and case studies illustrated the operability of this method and its advantages compared to random sampling.